2015
DOI: 10.2169/internalmedicine.54.2623
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Inflammatory Pseudotumor Associated with Xanthogranulomatous Cholangitis Mimicking Cholangiocarcinoma

Abstract: Inflammatory pseudotumor (IPT) is a rare benign condition often misdiagnosed as malignancy. An 80-year-old man was referred to our clinic for an asymptomatic hepatic mass detected on plain abdominal CT. Abdominal ultrasonography identified the lesion as a poorly defined hypoechoic mass. Although a liver biopsy did not provide any evidence of malignancy, imaging modalities suggested a diagnosis of cholangiocarcinoma. The patient underwent left lobectomy, and the pathological findings were consistent with the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…The etiology of hepatic IPT remains unknown. However, several factors, such as infection, trauma, biliary obstruction and cholangitis, autoimmune disorders, hepatitis B virus, hepatitis C virus, IgG4-related cholangitis and primary sclerosing cholangitis, are thought to be closely related to hepatic IPT (12)(13)(14). The present case had undergone percutaneous transhepatic liver abscess drainage six months earlier.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The etiology of hepatic IPT remains unknown. However, several factors, such as infection, trauma, biliary obstruction and cholangitis, autoimmune disorders, hepatitis B virus, hepatitis C virus, IgG4-related cholangitis and primary sclerosing cholangitis, are thought to be closely related to hepatic IPT (12)(13)(14). The present case had undergone percutaneous transhepatic liver abscess drainage six months earlier.…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that most cases with hepatic IPT were diagnosed after surgical resection (14). This is because of the lack of accurate diagnostic imaging methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ambiguity, the lesion completely resolves in some patients receiving antibiotics and/or corticosteroids, but some lesions recur [15][16][17]. Numerous studies have suggested surgery as the treatment of choice, particularly for patients with severe symptoms or an indeterminate diagnosis [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pseudotumor (IPT) is a rare benign condition reported in almost all organs, including occasionally in the liver [1]. IPT was first described in the lung in 1939 and liver involvement was first described in 1953 [2,3].…”
Section: Introductionmentioning
confidence: 99%